Answer: no soultions
Step-by-step explanation:
Answer:
32
Step-by-step explanation:
Answer:
Option C is correct.
Step-by-step explanation:
y = x^2-x-3 eq(1)
y = -3x + 5 eq(2)
We can solve by substituting the value of y in eq(2) in the eq(1)
-3x+5 = x^2-x-3
x^2-x+3x-3-5=0
x^2+2x-8=0
Now factorizing the above equation
x^2+4x-2x-8=0
x(x+4)-2(x+4)=0
(x-2)(x+4)=0
(x-2)=0 and (x+4)=0
x=2 and x=-4
Now finding the value of y by placing value of x in the above eq(2)
put x =2
y = -3x + 5
y = -3(2) + 5
y = -6+5
y = -1
Now, put x = -4
y = -3x + 5
y = -3(-4) + 5
y = 12+5
y =17
so, when x=2, y =-1 and x=-4 y=17
(2,-1) and (-4,17) is the solution.
So, Option C is correct.
Answer:
C?
Step-by-step explanation:
0.00000004 to the power of 4
Your answer would be <u>0</u>